PROBLEMS AND PROSPECTS OF INNOVATION DEVELOPMENT IN THE REPUBLIC OF KAZAKHSTAN - Kurbanbayeva A.A.,; Zhasulan D. M.,; Ussubaliyeva Saltanat Djumadilovna, (Academic Journal of Physical and Chemical Sciences, 2020)
The article considers the importance of innovative development of the Republic of Kazakhstan as one of the priority directions of economic growth in modern conditions. The main directions of the state policy in the sphere of scientific, technical and innovative activity are considered. Based on the research, important directions of innovation development in Kazakhstan have been identified. The purpose of the research is to study the problems of innovation development in the Republic of Kazakhstan and the innovative activity of Kazakhstani enterprises, the most important tools for implementing the strategy of innovative development and provide recommendations for their elimination. Methodology-the research process used such general scientific methods and techniques as scientific abstraction, analysis and synthesis, comparisons, generalizations, and descriptive analysis. Conclusions-successful implementation of state programs for innovative development of the country's economy should contribute to qualitative changes in the structure of the economy of Kazakhstan, which will lead it to sustainable growth based on the effective use of human, produced and natural capital, Kazakhstan's entry to a new level of social development and social structure. At the same time, the uncontrolled flow of foreign technologies can lead to the suppression of the development of the national research and production complex, which creates a real danger of technological dependence of the domestic industry on foreign developments.